Outcomes of people with TB reported to the WHO Global Clinical Platform of COVID-19 - M. Bastard; D. Falzon; S. Bertagnolio; R. Silva; S.S. Thwin; C. Siquiera Boccolini; J. Rylance; J. Diaz; M. Zignol (IJTLD Open)
BACKGROUND: TB is a leading infectious cause of death worldwide. The COVID-19 pandemic raised concerns that the burden of TB disease and death would increase due to the synergy between the two conditions. METHODS: We used individual-level data submitted to the WHO Global Clinical Platform for COVID-19 on hospitalised patients to explore associations of TB with mortality using multivariable logistic regression. RESULTS: Data were available from 453,233 persons with COVID-19 and known TB status and mortality outcomes from 62 countries (96% SARS-CoV-2 test-positive). Of these, 48% were male, and the median age was 53 years (IQR 38–67). There were 8,214 cases with current TB reported by 46 countries, mainly from Africa. Of people with current TB, 31.4% were admitted with severe illness, and 24.5% died. Current TB was independently associated with higher mortality when adjusted for age, sex, HIV status, illness severity at hospital admission, and underlying conditions (adjusted RR 1.47, 95% CI 1.35–1.61). CONCLUSION: Current or past TB were independent risk factors for in-hospital mortality regardless of illness severity at admission. Caveats for interpretation include changes during the data collection period (viral variation, vaccination coverage) and opportunistic sampling. However, the platform exemplifies how timely, coordinated global reporting can inform our understanding of health emergencies and the vulnerable populations affected.